Analisis Pelaksanaan Kebijakan Penangan Wabah Covid 19 di DKI Jakarta - Dede Saidah (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2020)
As the national capital, DKI Jakarta Province is very vulnerable to the spread of Covid-19. The Large-Scale Social Restriction Policy (PSBB) did little to reduce the rate of spread. The number of positive cases continues to grow exponentially. This paper aims to parse the various causes of the increasing number of positives, both in terms of government and society. This research uses qualitative methods and descriptive approaches. Based on the results of the discussion, it was found that various factors led to the uncontrolled spread of the virus, including: The slow response of the Central Government in deciding to take PSBB steps, overlapping policies, the lack of synergy of local governments in implementing PSBB policies, and many residents who did not comply with the policy.